Study of Inventory Model for Deteriorating Items With Exponential Demand Function - Mondal, Manik; Uddin, Mohammed Forhad; Hussain, Kazi Anowar (GANIT: Journal of Bangladesh Mathematical Society, 2016)
This paper develops an inventory model for deteriorating items consisting the ordering cost, unit cost, opportunity cost, deterioration cost and shortage cost. In this inventory model instead of linear demand function nonlinear exponential function of time for deteriorating items with deterioration rate has been considered. The formulated model has numerically solved by bisection method. The effects of inflation and cash flow are also taken into account under a trade-credit policy of discount with time. In order to validate the model, numerical examples have been solved by bisection method using Matlab. Further, the sensitivity of different parameters is considered in order to estimate the cash flow. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 89-100